Need for a Systematic Interview Process for Quality Work in the Organizations- An Empirical Analysis (A Suggestive Approach) - N Rajavel (Journal of Advanced Research in HR and Organizational Management, 2021)
Today, every organization needs excellent, qualified, dedicated, hardworking human resources with technology, education and health to maintain the Quality in the Organization. So the right qualified human resources are to be selected through a meaningful and well organized selection process. There are excellent and experienced experts in selecting the right candidates for the job for which they are conducting interview. Now the question is how the members are selected for the Interview Board, Selection Committee, Selection Board, and Screening Committee to carry out the process. Whether the employer is really adopting any principled procedure is biggest question? Normally whoever it is, there will be an interview fear and fever with slight tension to every candidate. Now days unwanted questions and unrelated questions are occupying the maximum space of time in the interview. All views of the candidate are to be carefully examined. Of all the interviewers must know the purpose for which the candidate is going to be selected and he is going to select the candidate. If the right candidates are selected, the productivity, potentiality, quality, speed-ness etc., will improve. The interviewers often fail to understand that their main function, duty and the responsibility is to select a right candidate. What mistake they commit is that as soon as the candidate enters the room, they start firing the candidates with the non-stop questions. The candidate will, there itself, loose his confidence about the interview & his selection, and forget all his subjects and preparations. Few interviewers are more careful to confuse and avoid the candidates rather than selecting the right candidates for the job. For that purpose, the employers have to carefully select the Interviewers rather than the candidates. The quality of the interviewers will definitely reflect in the selected candidates. So the selection of interviewers is the major task of the employers. It is the duty of the interviewers to select a right candidate for the job in the interview for which they are appointed. Useful suggestions are offered about how to conduct interview in the process of selection to maintain Quality Work in Organizations. How to cite this article: Rajavel N. Need for a Systematic Interview Process for Quality Work in the Organizations- An Empirical Analysis(A Suggestive Approach). J Adv Res HR Organ Mqmt 2021; 8(1&2)